Pesantren dan Konflik Keluarga: (Studi Kasus Pesantren Alfadiliyah Ciamis) - Aripudin, Acep (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
The fall of pesantren have been many differents problem one and the other. In the case of Alfadiliyah in this research has been many problems: first, leadership factor, which the successor of kyai leadership from old leaders to present has not followed normally method in generally tradisional pesantren; second, there are reformation movement on understanding and tradisional practices of culture pesantren which done by generation leader pesantren after die founder. Reformation Â movement like it mede opportunity to struggle from internal leader family, so stimulating struggle and conflict in pesantren; third, genetical factor as the influenced situation from many problems is competition in to pesantren assets, like materials, roles and power.